Glyphosate: Surfactant herbicide poisoning - Is it mild? - K Venugopal (Medical Journal of Dr. D.Y. Patil University, 2015)
Glyphosate Surfactant is a nonselective widely used herbicide in agriculture, forestry, industrial weed control, lawn, garden and aquatic environments. They have favorable toxicity with occupational and accidental exposures. The toxicity in humans is mucosal and gastrointestinal irritation, hypotension, metabolic acidosis, pulmonary insufficiency, and oliguria. Patient may appear asymptomatic for many hours before slowly lapse into a hypotensive, apparently nonhypovolaemic shock that can often ends fatally. We hereby report a case of a 25-year-old male patient who was admitted to our tertiary care hospital following suicidal consumption of around 250-300 ml of herbicide containing glyphosate (glypho; ). Initially, gastric lavage done and the patient was managed with intubation and mechanical ventilation. He also developed acute renal failure, and renal function reverted to normal after four sittings of hemodialysis. Patient was successfully treated and discharged home. This case report emphasizes on timely systemic supportive measure as the sole method of treatment since this poison has no specific antidote.